Meningkatkan Literasi Perbankan Syariah dengan Mengembangkan Aplikasi Edukasi Berbasis Android - Sibagariang, Yola Aprilia; Padli Nasution, M. Irwan (MES Bogor, 2023)
The purpose of this research is to be a form of research that wants to know the extent to which the level of use of android applications on the literacy level of respondents is already much better or significantly increased. In conducting this research, the researcher used a qualitative method with independent variables where the object of this research was an employee at the Baitul Yatama Fadlan Foundation which took a period of 2 days. The results that have been achieved in this study are increasing employee literacy at the Baitul Yatama Fadlan Foundation regarding Islamic banking which is quite effective by using an android application. It can be seen from the survey results which show that in the first survey, 47 percent, which then rose to 67 percent who already knew about Islamic banking. An android application that is considered quite significant in improving employee literacy at the Baitul Yatama Fadlan Foundation. Keywords: Islamic Banking Literacy, Consumer Loyalty, Android Application.